Intradermal vaccination of live attenuated influenza vaccine protects mice against homologous and heterologous influenza challenges - Andrew Chak-Yiu Lee (Nature Portfolio, 2021)
Abstract We previously developed a temperature-sensitive, and NS1 gene deleted live attenuated influenza vaccine (DelNS1-LAIV) and demonstrated its potent protective efficacy in intranasally vaccinated mice. Here we investigated whether intradermal (i.d.) vaccination induces protective immunity. Our results showed that DelNS1-LAIV intradermal vaccination conferred effective and long-lasting protection against lethal virus challenge in mice. A single intradermal injection of DelNS1-LAIV conferred 100% survival with no weight loss in mice after A(H1N1)09 influenza virus (H1N1/415742Md) challenge. DelNS1-LAIV injection resulted in a significant reduction of lung viral load and reduced airway epithelial cell death and lung inflammatory cytokine responses at day 2 and 4 post challenge. Full protections of mice lasted for 6 months after immunization. In vitro infection of DelNS1-LAIV in monocyte-derived dendritic cells (MoDCs) demonstrated activation of antigen-presenting cells at 33 °C, together with the results of abortive replication of DelNS1-LAIV in skin tissue and strong upregulation of inflammatory cytokines/chemokines expression, our results suggested the strong immunogenicity of this vaccine. Further, we demonstrate that the underlying protection mechanism induced by intradermal DelNS1-LAIV is mainly attributed to antibody responses. Together, this study opens up an alternative route for the administration of LAIV, which may benefit individuals not suitable for intranasal LAIV immunization.